Myth, Semiotics and Ideology: Carol Ann Duffy’s ‘from Mrs Tiresias’ and ‘Medusa’ - Zümrüt Altındağ (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2026)
Many modernist poets treated myth as the logos and regarded the revival of myth as the miraculous remedy to the trauma of the late 19th and early 20th centuries. T. S. Eliot (1975) in his reflection on James Joyce’s Ulysses, ‘Ulysses, Order, and Myth’, celebrates myth as the unifying element, the transcendental signified, of the fragmented western world. However, in the contemporary poststructuralist world, feminist critics, many women poets and writers reject the redemptive function of myth and its rationalisation of the subordination of women. Carol Ann Duffy is one of the contemporary British poets, who challenges the alliance between myth and phallogocentric discourse and attacks the representation of women in the western masculinized mainstream literary canon. By manifesting the ideological background to myth construction, with the poems published in The World’s Wife (1999), Duffy assumes an active role in the second wave feminist project of rewriting the patriarchal myths. In light of the semiological decoding of myth proposed by Roland Barthes in Mythologies, this papers analyses Duffy’s reduction of myth into systems of signification in the poems ‘from Mrs Tiresias’ and ‘Medusa.’